2012
DOI: 10.1162/pres_a_00126
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Feedback Improves Performance in a Palpation Task: Results in a VR-Based Testbed

Abstract: Robotic surgery provides many benefits such as reduced invasiveness and increased dexterity. This comes at the cost of no direct contact between surgeon and patient. This physical separation prevents surgeons from performing direct haptic exploration of tissues and organs, imposing exclusive reliance on visual cues. Current technology is not yet able to both measure and reproduce a realistic and complete sense of touch (interaction force, temperature, roughness, etc.). In this paper, we put forward a concept b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, with the widespread availability of small, low-cost actuators and controllers in the 1990s, the potential of wearable tactile displays became evident (Gallace, Tan, & Spence, 2007;Jones & Sarter, 2008). By the early 2000s, numerous studies had been conducted to evaluate the effectiveness of tactile displays in a variety of contexts from teleoperation (Kontarinis & Howe, 1995;Massimino & Sheridan, 1993) to navigation (Jones, Kunkel, & Piateski, 2009;van Erp, van Veen, Jansen, & Dobbins, 2005) and surgical training (Santos-Carreras, Leuenberger, Samur, Gassert, & Bleuler, 2012). Many of these studies demonstrated that vibrotactile displays are effective in assisting with spatial orientation and navigation in both real and virtual environments.…”
mentioning
confidence: 99%
“…However, with the widespread availability of small, low-cost actuators and controllers in the 1990s, the potential of wearable tactile displays became evident (Gallace, Tan, & Spence, 2007;Jones & Sarter, 2008). By the early 2000s, numerous studies had been conducted to evaluate the effectiveness of tactile displays in a variety of contexts from teleoperation (Kontarinis & Howe, 1995;Massimino & Sheridan, 1993) to navigation (Jones, Kunkel, & Piateski, 2009;van Erp, van Veen, Jansen, & Dobbins, 2005) and surgical training (Santos-Carreras, Leuenberger, Samur, Gassert, & Bleuler, 2012). Many of these studies demonstrated that vibrotactile displays are effective in assisting with spatial orientation and navigation in both real and virtual environments.…”
mentioning
confidence: 99%